2015
DOI: 10.1155/2015/518643
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Single Nucleotide Polymorphisms within ADAM12 and Risk of Knee Osteoarthritis in a Chinese Han Population

Abstract: Objective. Osteoarthritis (OA) is a complex arthritic condition in which the genetic factor plays a major role. One of the candidate genes of is the ADAM12 gene, but no consistency has been reached till now. This study aims to investigate the potential role of four single nucleotide polymorphisms (SNPs) of the ADAM12 gene in susceptibility to knee OA and its progression in Chinese Han population. Methods. The rs1278279, rs3740199, rs1044122, and rs1871054 polymorphisms were genotyped and compared in a populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 22 publications
2
30
0
2
Order By: Relevance
“…The extremely high OR values among males might be partly attributed to the insufficient sample size or selection bias. In addition, some of the extracted ORs with their 95% CIs originated from multivariate analyses and were adjusted for potential confounders 4,5,12,16. On the other hand, some ORs were given from the univariate model 6,10,18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extremely high OR values among males might be partly attributed to the insufficient sample size or selection bias. In addition, some of the extracted ORs with their 95% CIs originated from multivariate analyses and were adjusted for potential confounders 4,5,12,16. On the other hand, some ORs were given from the univariate model 6,10,18.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that rs3740199 is associated with OA susceptibility among the general population,9 or certain groups of the studied participants 6,10. Apart from disease vulnerability, ADAM12 mutation has also been linked to OA severity 5. However, studies that did not observe any positive association of ADAM12 SNP with OA also exist among various races 11,12.…”
Section: Introductionmentioning
confidence: 95%
“…Finally, six case-control studies focusing on four ADAM12 polymorphisms (rs3740199, rs1871054, rs1278279, and rs1044122) and knee OA risk were included in this meta-analysis. [12][13][14][15][16][17] Among them, since one study was conducted at three centers 17 and one study analyzed tibiofemoral joint and patellofemoral joint OA separately, 16 a total of nine studies included 2,966 cases and 4,901 controls. Four studies were conducted on Asian subjects and five studies were conducted in European subjects.…”
Section: Resultsmentioning
confidence: 99%
“…There were no restrictions on race, language, ethnicity, or geographic area. 13 The baseline information was extracted, such as the first author, year of publication, country and sex of the study population, type and grade of OA in case groups, number of cases and controls, results of the Hardy-Weinberg equilibrium (HWE) test, and allele and genotype frequencies of ADAM12. In cases of duplicated publications from the same study group, the study with a larger sample size was retained.…”
Section: Methodsmentioning
confidence: 99%
“…This ADAM has been associated with OA in genetic studies, 41,42 and ADAM12 mRNA and protein (by immunocytochemistry) levels are upregulated in end-stage OA cartilage. 22,23 ADAM12 plays a role in chondrocyte proliferation through cleavage of insulin-like growth factor binding protein (IGFBP)-5, 22 which may be important in attempted repair by chondrocytes in OA.…”
Section: Adam12mentioning
confidence: 90%